Cohesion and differentiation in Australia's elite suburbs. (8th December 2017) - Wiesel, Ilan; Levin, Iris
Abstract: Toorak (Melbourne) and Mosman (Sydney) are two of the most affluent suburbs in Australia. The high costs of living and housing in these suburbs preserve their high status. Yet, in recent years, the growing presence of wealthy Chinese residents and investors has challenged longstanding Anglo‐Australian residents' perceptions of these suburbs as "European villages". At the same time as new shared identities are being produced, feelings of resentment and anxiety are also increasingly being expressed through local urban planning conflicts related to density and heritage in residential development. Drawing on theories of "elite integration", and interviews with 35 residents of the two suburbs the paper exposes a range of spatial, material, and discursive practices through which the Australian elite manages ethnic diversity within its suburban strongholds.